2006
DOI: 10.1159/000093769
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Eosinophil Activation before and after Food Challenges in Adults with Food Hypersensitivity

Abstract: Background: Objective assessment of inflammatory reactions in the gastrointestinal tract could be useful in the diagnosis of food hypersensitivity. The aim of the present study was to investigate the involvement of eosinophils and mast cells in the inflammatory response of patients with food hypersensitivity before and after food challenges. Methods: Eleven patients (4 with IgE-mediated allergy and 7 without) with food hypersensitivity and positive double-blind, placebo-controlled food challenge were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…4 Although the involvement of mast cells in food allergies is well recognized, 5 increasingly, several studies have indicated a role for eosinophils in promoting food allergen-induced inflammation. Experimental animal models of food antigen-driven GI inflammation [6][7][8] as well as studies in patients with food allergies [9][10][11] show that eosinophils are recruited to the intestinal mucosa in substantial numbers. Although present in the normal GI mucosa under homeostatic conditions, 12 eosinophils are known to contribute to inflammation when present in abnormal numbers.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although the involvement of mast cells in food allergies is well recognized, 5 increasingly, several studies have indicated a role for eosinophils in promoting food allergen-induced inflammation. Experimental animal models of food antigen-driven GI inflammation [6][7][8] as well as studies in patients with food allergies [9][10][11] show that eosinophils are recruited to the intestinal mucosa in substantial numbers. Although present in the normal GI mucosa under homeostatic conditions, 12 eosinophils are known to contribute to inflammation when present in abnormal numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory disorders such as inflammatory bowel disease may be discriminated from IBS with the use of the neutrophil-derived protein calprotectin in stool 14 17 . Food allergies, which have a reported prevalence rate of about 25% in IBS patients, 18 may be suggested by the presence of elevated fecal levels of eosinophil protein X, which may also be elevated in inflammatory bowel disorders and parasitic infections 19 25 . Pathogenic infections such as Clostridium difficile and parasites such as Giardia lamblia are reported in 5.7% and 6.5%, respectively, of people with symptoms attributable to IBS 26 , 27 and are readily detected on fecal specimens using established techniques such as culture and light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Food allergies, which have a reported prevalence rate of about 25% in IBS patients, 18 may be suggested by the presence of elevated fecal levels of eosinophil protein X, which may also be elevated in inflammatory bowel disorders and parasitic infections. [19][20][21][22][23][24][25] Pathogenic infections such as Clostridium difficile and parasites such as Giardia lamblia are reported in 5.7% and 6.5%, respectively, of people with symptoms attributable to IBS 26,27 and are readily detected on fecal specimens using established techniques such as culture and light microscopy. Blastocystis hominis, the most common human intestinal parasite, was long thought to be non-pathogenic.…”
mentioning
confidence: 99%
“…It is generally agreed that food additives in particular AFCs may cause non-IgE-mediated intolerance reactions in some predisposed individuals or sub populations causing asthma, rhinitis, urticaria, itchiness, and migraines in largely unidentified mechanisms (Orlatoniand Pastorello, 2006;Stevens et al, 2013). Studies, nevertheless, suggest hypersentivity reactions to food antigens could possibly be associated with inflammatory cells like eosinophils, neutrophils and mast cells (van Odijk et al, 2006;Stevens et al, 2013). Especially, neutrophils, of late are being identified, as playing critical role in allergic inflammatory processes giving rise to immense interest in these fascinating cells (Mocsai, 2013;Gunzer, 2014).…”
Section: Discussionmentioning
confidence: 99%